PENGARUH KUALITAS SISTEM, KUALITAS INFORMASI, DAN KUALITAS PELAYANAN TERHADAP PENGGUNAAN SMART GOVERNMENT DI KABUPATEN LAMPUNG SELATAN - Novera Anjarbati; Ulung Pribadi (Universitas Jenderal Ahmad Yani, 2022)
The application of the concept of smart government in the region is certainly an interesting thing to study because each region has its problems and efforts in realizing the concept, one of which is in the South Lampung Regency. The implementation of smart government in South Lampung Regency is one of them with the online population administration service website (PAKe-Oli). The innovation of the program is present to meet the needs of the community related to basic services, facilitate the community, effectively, efficiently by the concept of smart government to realize an orderly society of population administration. The purpose of this study is to analyze and explain the influence of system quality, information quality and quality of service on the use of smart government by the South Lampung Regency Government. Using quantitative research methods, the results of this study explain that the quality of the system, the quality of information and the quality of services have a positive and significant effect on the use of smart government in South Lampung Regency in 2021. Evidenced by hypothesis tests that show that these three variables affect the use of smart government positively and significantly.